Analyzing hydroponic rack design for apartment house - Talib, Mohd Hafiz; Abd Rahman, Khairul Aidil Azlin; Dollah, Mohd Shahrizal (Science Publishing Corporation, 2018)
This study analyze users who are living in condominium and apartment in an urban area to practice the farming activity. Almost 75% type of house in Malaysia is apartment. A major problem living in condominium and apartment is the limited space to do farming activity. To-day's users do not know where their food comes from and uncontrolled using pesticide among the farmers. Over 80% of food supplies were imported and local crops products were exported. About 65% from a person salary is for food consumption. The existing design of hydroponic system is not suitable for the current lifestyle needs. This help users to farm within a limited space in the urban area and create awareness the importance of planting their own food. Hydroponic system can reduce 40% of living cost for food. The compact rack system design has been proposed based on the functionality and practicality for crops planting in a small area using deep water culture system. The compact rack design using a simple system that can easy to assemble and disassemble that suit home interior. The result shows the hydroponic rack with modular system is suitable for the condominium and apartment area which are small and compact.